Pendidikan Islam Berbasis Moderasi Beragama: Pendekatan Pedagogis Kritis dan Multikultural - Fawaz Fawaz (STAI Darul Kamal NW Kembang Kerang, 2026)
This article examines the role of Islamic education in strengthening religious moderation literacy within Indonesia’s plural society. It argues that Islamic education should move beyond a merely normative mode of instruction toward a reflective, contextual, and socially responsive formation of religious reasoning. The study employs a qualitative approach based on library research enriched by limited empirical reading of classroom practices and curriculum documents. The findings suggest that religious moderation literacy should be understood as an epistemological framework connecting religious texts, social context, and educational praxis. Strengthening moderation in Islamic education requires curriculum reconstruction, dialogical-critical pedagogy, teacher reinforcement, and an inclusive educational environment. The article contributes an integrative input–process–output–outcome model for developing moderate Islamic education relevant to diversity.